Differential Susceptibility to T Cell-Induced Colitis in Mice: Role of the Intestinal Microbiota. Issue 2 (18th January 2018) - Reinoso Webb, Cynthia; den Bakker, Hendrik; Koboziev, Iurii; Jones-Hall, Yava; Rao Kottapalli, Kameswara; Ostanin, Dmitry; Furr, Kathryn L; Mu, Qinghui; Luo, Xin M; Grisham, Matthew B
Abstract: One of the best characterized mouse models of the inflammatory bowel diseases (IBD; Crohn's disease, ulcerative colitis) is the CD4 + CD45RB high T cell transfer model of chronic colitis. Following our relocation to Texas Tech University Health Sciences Center (TTUHSC), we observed a dramatic reduction in the incidence of moderate-to-severe colitis from a 16-year historical average of 90% at Louisiana State University Health Sciences Center (LSUHSC) to <30% at TTUHSC. We hypothesized that differences in the commensal microbiota at the 2 institutions may account for the differences in susceptibility to T cell-induced colitis. Using bioinformatic analyses of 16S rRNA amplicon sequence data, we quantified and compared the major microbial populations in feces from healthy and colitic mice housed at the 2 institutions. We found that the bacterial composition differed greatly between mice housed at LSUHSC vs TTUHSC. We identified several genera strongly associated with, and signficantly overrepresented in high responding RAG -/- mice housed at LSUHSC. In addition, we found that colonization of healthy TTUHSC RAG -/- mice with feces obtained from healthy or colitic RAG -/- mice housed at LSUHSC transferred susceptibility to T cell-induced colitis such that the recipients developed chronic colitis with incidence and severity similar to mice generated at LSUHSC. Finally, we found that the treatment of mice with preexisting colitis with antibiotics remarkably attenuated disease. Taken together, our data demonstrate that specific microbial communities determine disease susceptibility and that manipulation of the intestinal microbiota alters the induction and/or perpetuation of chronic colitis.